A comparative analysis of two rowing ergometer tests in elite female rowers - Hsieh, S. S.; Wu, S. S. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of this study was to compare the physiological indices between a 6-minutes all-out (ao) and a progressive incremental (pi) rowing ergometer tests. Summary: The progressive incremental (pi) rowing ergometer test can be used to estimate the maximum oxygen consumption, the exercise intensities and heart rates corresponding to anaerobic threshold and lactate threshold, and the relationship of blood lactate to exercise intensities. it may also provide a basis for estimating anaerobic capacity. a 6-minutes all-out (ao) rowing ergometer test was used to simulate a rowing race. The pi and ao tests have specialized advantages, and two kinds of tests have used by rowing coach and sport scientist. Even though the procedure of pi test and analysis of physiological data cost more time than the ao test, its capacity on assessing rowing performance is more complete than the ao test.